Pemberdayaan Pemasaran Produk dan Karya Bagi Organisasi Disabilitas Tuban Melalui Pelatihan Pemasaran Multichannel Terpadu - Rudi Wibowo; Nuning Nurna Dewi; Imransyah; Muhammad Azwar Anas (Universitas Muhammadiyah Malang, 2026)
Purpose – This Community Service Program (PKM) aims to empower Orbit through Integrated Multichannel Marketing Training by integrating online (social media, marketplace) and offline (exhibitions, local networks) marketing strategies. Design/methodology/approach – The program was implemented using a participatory approach, encompassing outreach and needs mapping, comprehensive training, guided technology implementation, mentoring, and strengthening program sustainability. The training focused on digital marketing skills, simple business management, and product branding. Evaluation was conducted through pre-tests, post-tests, observation, and documentation. Findings – Results showed significant improvements in participants' understanding and skills, with the average score increasing from 61.2 to 86.5 after the training. Participants were able to create business accounts, manage online stores in marketplaces, and produce simple, engaging promotional content. The program also generated follow-on impacts such as the formation of an internal learning community, the emergence of local champions as peer mentors, and increased market reach for products for people with disabilities. Originality/value – Overall, this PKM activity strengthens the capacity of disability organizations in marketing, encourages economic independence, and increases socio-economic inclusion in Tuban Regency.